2014
DOI: 10.1021/jp503960q
|View full text |Cite
|
Sign up to set email alerts
|

Formation of RuO(OH)2 on RuO2-Based Electrodes for Hydrogen Production

Abstract: The catalytic and durable electrode coating of ruthenium dioxide (RuO2), applied on nickel (Ni) substrates, is today utilized as electrocatalytic cathodes for hydrogen production, e.g., in the chlor-alkali process and alkaline water electrolysis. The drawback is, however, the sensitivity to reverse currents obtained during power shutdowns, e.g. at maintenance, where the RuO2-based electrodes can be severely damaged unless polarization rectifiers are employed.Through the material characterization techniques X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 29 publications
7
65
1
Order By: Relevance
“…In contradiction to earlier conclusions, we have in a recent work showed that metallic ruthenium, in fact, is formed during hydrogen evolution in an alkaline electrolyte and at high current density [18]. The study further shows that the RuO2 coating, prior to metallic Ru formation, is subjected to a transformation into ruthenium oxyhydroxide (RuO(OH)2).…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contradiction to earlier conclusions, we have in a recent work showed that metallic ruthenium, in fact, is formed during hydrogen evolution in an alkaline electrolyte and at high current density [18]. The study further shows that the RuO2 coating, prior to metallic Ru formation, is subjected to a transformation into ruthenium oxyhydroxide (RuO(OH)2).…”
Section: Introductioncontrasting
confidence: 99%
“…Nickel content in RuO2 coatings applied on Ni substrates has been confirmed with XPS [18]. The study showed that a RuO2 coating of a newly made electrode has a substantial amount of nickel oxide (NiO), which after exposure to hydrogen evolution transforms into Ni(OH)2 and metallic Ni.…”
Section: Effect Of Her Oer and Reverse Currentsmentioning
confidence: 75%
See 3 more Smart Citations